Fostering the Best Execution Regime An Experiment about Pecuniary Sanctions and Accountability in Fiduciary Money Management - Alec Sproten; Sandro Casal; Matteo Ploner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Asset management often involves a conflict of interests between investors and fund managers. A main goal of financial regulators is to identify and mitigate this conflict. This article focuses on measures that may foster protection of investors' interests. In an experiment capturing the essential elements of asset management, we find that managers' accountability does not prevent their opportunistic behavior if not backed by a threat of punishment. Further, investors inefficiently sanction managers if not completely aware of managers' choices. To effectively protect investors in financial intermediations, financial regulators should ensure both managers' accountability and a credible sanctioning system.
Keywords: C70; D02; C91; 330